2011
DOI: 10.1103/physreve.84.016301
|View full text |Cite
|
Sign up to set email alerts
|

Resonance phenomenon for the Galerkin-truncated Burgers and Euler equations

Abstract: It is shown that the solutions of inviscid hydrodynamical equations with suppression of all spatial Fourier modes having wave numbers in excess of a threshold K(G) exhibit unexpected features. The study is carried out for both the one-dimensional Burgers equation and the two-dimensional incompressible Euler equation. For large K(G) and smooth initial conditions, the first symptom of truncation, a localized short-wavelength oscillation which we call a "tyger," is caused by a resonant interaction between fluid p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(138 citation statements)
references
References 25 publications
5
132
1
Order By: Relevance
“…However, as shown in Ref. [17], at t = t , at points which have the same velocity as the shock(s), Ψ = 0 and a symmetric, localised, monochromatic bulge, called tyger by Ray, et al [17], forms as shown in Fig. 2 (inset).…”
Section: Tygers and Thermalisationmentioning
confidence: 72%
See 3 more Smart Citations
“…However, as shown in Ref. [17], at t = t , at points which have the same velocity as the shock(s), Ψ = 0 and a symmetric, localised, monochromatic bulge, called tyger by Ray, et al [17], forms as shown in Fig. 2 (inset).…”
Section: Tygers and Thermalisationmentioning
confidence: 72%
“…We begin by performing direct numerical simulations of equations (1) and (4), without any loss of generality [17,18], with initial conditions u 0 (x) = v 0 (x) = sin(x + φ), where φ = 0.7 is a phase which shifts the location of the cubic singularity away from x = π. For such an initial condition, it is easy to show that t = 1.0 [28,29].…”
Section: Tygers and Thermalisationmentioning
confidence: 99%
See 2 more Smart Citations
“…As soon as we introduce the fractal decimation projector, several sharp oscillatory structures appear in the solution for v(x, t), even for mild decimation (D 1), as seen in Fig 1(b). Such structures, although reminiscent of features (tygers) of the Galerkin-truncated Burgers equation [22], are crucially different because they are spatially much more delocalized.…”
Section: The Burgers Equation On a Fractally Decimated Fourier Setmentioning
confidence: 99%